The independent effects of vitamin D deficiency and house dust mite exposure on lung function are sex-specific. Issue 1 (December 2017) - Nuñez, Nailê; Bennett, Ellen; Chen, Ling; Pitrez, Paulo; Zosky, Graeme
Abstract Vitamin D deficiency is increasing around the world and has been associated with the development of asthma. This study aims to evaluate the effect of dietary vitamin D deficiency at different life stages on lung function using a murine model of allergic airways disease. BALB/c mice were challenged intranasally with HDM or saline alone for 10 days. Twenty four hours after the last challenge, mice were anesthetized and lung function was measured using the forced oscillation technique (FOT). Mice were euthanized for assessment of inflammation in the bronchoalveolar lavage (BAL) and total collagen content in lung homogenates by ELISA. Vitamin D deficiency impaired lung function in both male and female mice, increasing tissue damping and elastance, however had no effect on HDM induced inflammation. The impact of vitamin D deficiency was more evident in females. HDM also decreased airway distensibility, but only in females and this response was not altered by vitamin D deficiency. Our data suggest that vitamin D deficiency and HDM exposure have independent effects on lung mechanics and that females are more susceptible to these effects. Vitamin D deficiency may exacerbate lung function deficits by having a direct, but independent, effect on parenchymal mechanics.